The brain death definition and human organs transplantation in the light of the Catholic Church teaching - Dudzińska, Joanna; Dobrowolska, Beata (Nursing in the 21st Century, 2016)
THE BRAIN DEATH DEFINITION AND HUMAN ORGANS TRANSPLANTATION IN THE LIGHT OF THE CATHOLIC CHURCH TEACHINGAim. The aim of this paper is to present the teaching of the Catholic Church regarding the brain death and the human organ transplantation.Material and methodology. The analysis of the official documents of the Holy See as well as the teaching and speeches of popes was made.Results and conclusions. The Catholic Church supports transplants from deceased persons and considers donating their organs after death for transplantation as the gift of the greatest love. However, it is not unconditional acceptance. The most important conditions are: the patient’s informed consent for organ donation and a precise statement of the death of the donor. The currently used definition of brain death has been declared by the Church not only as sufficient but also as definitive criterion of the death of a man. In Christian ethics, this criterion allows an ethical judgment, which is called as moral certainty and provides the basis for an ethically proper action. It is also stressed that the donation of organs for transplantation must be altruistic. It is unacceptable to expect and to receive any payment for such an act.